Measurement of the azimuthal anisotropy of charged particles produced in √sNN = 5.02 TeV Pb+Pb collisions with the ATLAS detector - Alconada Verzini, María Josefina (2018)
Measurements of the azimuthal anisotropy in lead–lead collisions at √sNN = 5.02 TeV are presented using a data sample corresponding to 0.49 nb−1 integrated luminosity collected by the ATLAS experiment at the LHC in 2015. The recorded minimum-bias sample is enhanced by triggers for “ultra-central” collisions, providing an opportunity to perform detailed study of flow harmonics in the regime where the initial state is dominated by fluctuations. The anisotropy of the charged-particle azimuthal angle distributions is characterized by the Fourier coefficients, v2–v7, which are measured using the two-particle correlation, scalar-product and event-plane methods. The goal of the paper is to provide measurements of the differential as well as integrated flow harmonics vn over wide ranges of the transverse momentum, 0.5 < PT < 60 GeV, the pseudorapidity, |η| < 2.5, and the collision centrality 0–80%. Results from different methods are compared and discussed in the context of previous and recent measurements in Pb+Pb collisions at √ sNN = 2.76 TeV and 5.02 TeV. In particular, the shape of the PT dependence of elliptic or triangular flow harmonics is observed to be very similar at different centralities after scaling the vn and PT values by constant factors over the centrality interval 0–60% and the pT range 0.5 < PT < 5 GeV.